Justifikasi Hak Politik Mantan Narapidana: Perspektif Hak Asasi Manusia dan Perundang-Undangan - Cipto Prayitno (The Constitutional Court of the Republic of Indonesia, 2020)
Decision of the Supreme Court Number 46 P/HUM/2018 regarding judicial review which invalidates the provisions of the Article 4 paragraph (3) of the General Election Commission Regulation Number 20 Year 2018 which states the prohibition of including candidates who are ex-convicts of drug cases, sexual crimes and corruption. However, the enactment of General Election Commission Regulation triggered pros and cons. On the one hand, the substance of the regulation regulates the prohibition and revoking the political rights of ex-convicted and contrary with the higher regulations, because it regulates the contrary substance with higher regulation. But on the other hand, this is a progressive step which is the hope for parties to shown the good image and free corruption legislative bodies. This paper raises 2 (two) problem formulations are (1) how is the regulation through the Election Commission Regulation related to political rights of convicted corruption cases and (2) how is the justification of the Human Rights dimension of the political rights of ex-corruption convicted. The purpose of this paper is to examine and find out how the General Election Commission Regulation Number 20 Year 2018 regulates the political rights of ex-corruption convicted as well as legal implications of the Supreme Court Decision Number 46 P/HUM/2018 towards General Election Commission Regulation Number 20 Year 2018. This study specifically uses normative legal method through library research and analyzed systematization into a descriptive analytical paper. The results showed that the enactment of the Election Commission Regulation that normalized the prohibition of passive political rights for ex-convicts contained several weaknesses and ultimately annulled by the Supreme Court’s Decision. Viewed from the perspective of Human Rights related to political-rights, in its application, there must be a limitation in the time of the revocation of rights.